2005
DOI: 10.5380/avs.v10i3.5125
|View full text |Cite
|
Sign up to set email alerts
|

Utilização Do Grão De Cevada Em Substituição Ao Milho Em Dietas Para Vacas Em Lactação

Abstract: Autor para correspondência: André Thaler Neto -thaler@cav.udesc.br.RESUMO -O objetivo deste trabalho foi avaliar os efeitos da substituição total e parcial de grãos de milho moídos por grãos de cevada laminados sobre a produção e a composição do leite. Foram utilizadas 28 vacas holandesas, com média de 125 dias de lactação, em um delineamento em quadrado latino 4x4. A dieta foi fornecida na forma de dieta totalmente misturada, 1 vez ao dia. Foram testados 4 níveis de substituição de milho por cevada (T1 -0% ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The level of CP from BR (17.77%) is better than that from corn and lower than wheat, but it is nevertheless considered to have the lowest quality and digestibility (Zardo and Lima 1999). Cardova et al (2004), in a study on dairy cows, tested the replacement of maize with barley by-products and found that the average proportion of barley inclusions increased NDF and ADF. For these reasons, several trials on dairy cows have been conducted to study the effect of using different flax forms (seed, meal and oil) to compare their effects with other sources on milk production and composition.…”
mentioning
confidence: 99%
“…The level of CP from BR (17.77%) is better than that from corn and lower than wheat, but it is nevertheless considered to have the lowest quality and digestibility (Zardo and Lima 1999). Cardova et al (2004), in a study on dairy cows, tested the replacement of maize with barley by-products and found that the average proportion of barley inclusions increased NDF and ADF. For these reasons, several trials on dairy cows have been conducted to study the effect of using different flax forms (seed, meal and oil) to compare their effects with other sources on milk production and composition.…”
mentioning
confidence: 99%